Visual representations in the novels of Amirkhan Yeniki and Oleg Sagan-ool - Arzamazov, Alexey A.; Dolzhikova, Angela V. (The New Research of Tuva, 2024)
The article discusses the representation of visuality in the texts of two Turkic literary works — Tatar and Tuvan literature. The sources used for this analysis are the novels “Gulandam” (1977) and “The Expendables” by Oleg Sagan-ool, which were translated into Russian. The artistic representation of vision reflects the objective and subjective psychological and physiological abilities of an individual, as well as the unique nature of creative self-expression. It also explores the diverse ethnocultural contexts and interactions between different forms of art. During the analysis, several visual components were identified (portraits of characters, natural landscapes, figurative associations, comparisons, “spaces” of memory, dreams in visual form). Some stadial-typical, ethnospecific and individual-authorial features of the visual representation were recorded. Eniki’s novel focuses on the portrayal of representatives of the new Soviet Tatar intelligentsia and touches on the relationship between music and visual arts. O. Sagan-ool describes the rural life of the Tuvan people in the context of the first collective farms, emphasizing the external features of his characters. He consistently reveals the ethnocultural element and shows the difficulties of interpersonal communication through his versatile descriptions. The question arises about the development of criteria for identifying visual parameters in a literary text and the system of literature.